The dugout canoe from São Tomé and Principe. The results of an archaeo-anthropological mission - Baço, Joana; Lopes, Gonçalo (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The aim of this article is to present the findings of a research mission carried out in February 2020. The authors gathered evidence of the construction of wooden dugout canoes on the islands of São Tomé and Príncipe, with the goal of documenting and comprehending their manufacturing process, from the felling of the tree to their use on the water. This study analyses a very important element of the cultural tradition of an archipelago that is struggling to survive due to environmental problems, lack of interest from younger generations, and the introduction of fiberglass, a more durable and safer material.